Elevated cytomegalovirus IgG antibody levels are associated with HIV-1 disease progression and immune activation. (27th March 2017) - Patel, Eshan U.; Gianella, Sara; Newell, Kevin; Tobian, Aaron A.R.; Kirkpatrick, Allison R.; Nalugoda, Fredrick; Grabowski, Mary K.; Gray, Ronald H.; Serwadda, David; Quinn, Thomas C.; Redd, Andrew D.; Reynolds, Steven J.
Abstract : Objective: To assess the association between cytomegalovirus (CMV) IgG antibody levels, HIV disease progression, and immune activation markers. Design: A prospective cohort study was conducted among women enrolled in a trial that was designed to determine the effect of acyclovir on HIV disease progression in Rakai, Uganda. Methods: The primary endpoints were progression to a CD4 + T-cell count less than 250 cells/μl, nontraumatic death, or initiation of antiretroviral therapy (ART). CD4 + T-cell counts, HIV viral load, C-reactive protein (CRP), and soluble CD14 levels were assessed biannually for 24 months. CMV IgG antibodies were measured at baseline among all women and annually among a subset of women who initiated ART. Results: There were 300 HIV/CMV-coinfected participants who contributed a total of 426.4 person-years with a median follow-up time of 1.81 years. Compared with the lowest CMV IgG tertile group at baseline, the highest CMV IgG tertile group was associated with an increased risk to reach a primary endpoint independent of acyclovir use, age, CD4 + T-cell count, and HIV viral load at baseline [adjusted hazard ratio = 1.59; (95% CI = 1.05–2.39); P = 0.027]. Among pre-ART visits ( n = 1200), women in the highest baseline CMV IgG tertile had increasing annual rates of soluble CD14 and CRP levels, which was not observed for the low CMV IgG tertile group. Compared with pre-ART visits, CMV IgG antibody levels were higher post-ART initiation, and concurrent levels remained associated with soluble CD14 and CRP during suppressive ART ( n = 88 person-visits). Conclusion: The magnitude of the immune response to CMV was associated with HIV disease progression and immune activation in sub-Saharan Africa. Abstract : Supplemental Digital Content is available in the text